Research on teaching reform of accounting information system under the background of big intelligence and cloud - Zhan, Ximing; Xu, Huanhuan; Rathor, Shehkar (Economics & Management Review, 2025)
This paper explores the teaching reform of the Accounting Information System course in the context of Big Data, Intelligence, Mobile Internet, and Cloud Computing ("Big Data & Smart Cloud"). It analyses the challenges of traditional curriculum design in adapting to evolving financial industry demands, particularly the integration of digital technologies and professional ethics. The study proposes reforms in three key areas: embedding intelligent finance modules (e.g., financial robot applications) into teaching content, adopting problem-oriented and scenario-based teaching methods, and implementing a process-focused assessment system. By integrating ideological and political elements into professional education, the reform aims to cultivate accounting professionals with both technical proficiency and ethical awareness, capable of addressing big data challenges in rural ecotourism and other modern industries. Empirical results show enhanced student engagement and practical skills through case studies and industry expert involvement, highlighting the importance of interdisciplinary and technology-driven curriculum innovation.